Context-Dependent Parental Effects on Clonal Offspring Performance - Dong, Bi-Cheng; van Kleunen, Mark; Yu, Fei-Hai (Frontiers in Plant Science, 2018)
Parental environments may potentially affect offspring fitness, and the expression of such parental effects may depend on offspring environments and on whether one considers an individual offspring or all offspring of a parent. Using a well-studied clonal herb, Alternanthera philoxeroides, we first grew parent plants in high and low soil-nutrient conditions and obtained 1st generation clonal offspring from these two environments. Then we grew offspring of these two types of 1st generation clonal offspring also in high and low nutrient conditions. We measured and analyzed mean performance and summed performance of the four types of 2nd generation clonal offspring. High nutrient availability of parental environments markedly increased both mean performance (i.e., the average fitness measure across all individual offspring produced by a parent) and summed performance (i.e., the sum of the fitness measure of all offspring produced by a parent) of the 2nd generation clonal offspring. The positive parental effects on summed performance of the 2nd generation clonal offspring were stronger when the 1st generation clonal offspring grew in the high instead of the low nutrient conditions, but the positive parental effects on their mean performance did not depend on the nutrient environments of the 1st generation clonal offspring. The results provide novel evidence that parental environmental effects persist across vegetative generations and strongly depend on offspring environments and levels of plants.